2002
DOI: 10.1046/j.1365-2672.2002.01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli O157:H7 in farm water: its role as a vector in the transmission of the organism within herds

Abstract: Aims:The study aimed to investigate the survival characteristics of Escherichia coli O157:H7 in farm water (FW), and in sterile distilled municipal water (SDW), stored outdoors under field conditions, with or without the addition of faeces (1% w ⁄ v), in a farmyard shed and the laboratory at 15°C. Methods and Results: Water samples were inoculated with E. coli O157:H7 at 10 3 and 10 6 ml )1 , and sampled over a 31-day period. In FW stored outdoors in a field, E. coli O157:H7 survived for 14 days at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Survival results are in line with those reported in similar freshwater aquatic environments ranging from 12 to 260 days (47,48,49,50). In general, extended survival was enhanced by sterilization of the water prior to inoculation (47,48,51,52), indicating the role of grazing protozoa (47) and/or competition for limited resources with the indigenous microbial community (53). Survival was also strain dependent and influenced by temperature in the nontreated drinking water.…”
Section: Discussionsupporting
confidence: 86%
“…Survival results are in line with those reported in similar freshwater aquatic environments ranging from 12 to 260 days (47,48,49,50). In general, extended survival was enhanced by sterilization of the water prior to inoculation (47,48,51,52), indicating the role of grazing protozoa (47) and/or competition for limited resources with the indigenous microbial community (53). Survival was also strain dependent and influenced by temperature in the nontreated drinking water.…”
Section: Discussionsupporting
confidence: 86%
“…These E. coli O157:H7 reservoirs would likely be reduced or absent during the winter months. Environmental reservoirs likely exist in dairy heifer pens, although this has not been determined (15,26,29), and consequently, detection of E. coli O157:H7 only by enrichment fecal cultures (a method that detects as little as 1 CFU/g of feces [23]) and not by RAMS culture may reflect the passage of ingested E. coli O157:H7 rather than colonization.…”
Section: Discussionmentioning
confidence: 99%
“…An accepted premise is that the reduction of the number of cattle infected with E. coli O157:H7 or the elimination of E. coli O157:H7 from cattle will effect a reduction in the rate of disease in humans. To this end, a great deal of research has focused on describing the ecology and epidemiology of E. coli O157:H7 in cattle, with the hope of identifying interventions to reduce its prevalence in cattle (11,16,17,19,20,23,24,28,29). Within this body of research, numerous methods for detecting E. coli O157:H7 in bovine fecal samples have been developed and used (8,9,22,36,37,40).…”
mentioning
confidence: 99%
“…However, it should be noted that not all strains belonging to these serogroups will cause severe illness and that other non-O157 VTEC serogroups also cause illness. Pathogenic VTEC strains are categorized as enterohemorrhagic E. coli, and usually in these strains, a large outer membrane protein (94)(95)(96)(97) called intimin mediates the intimate contact between the bacterium and the enterocyte cytoplasmic membrane (attachment) and the destruction of the enterocyte microvilli (effacement). The genetic determinants for this (eae, tir, esc, and sep genes) are grouped together on the chromosome, forming a pathogenicity island called LEE, for locus of enterocyte effacement (7).…”
Section: Human Pathogenic Vtecmentioning
confidence: 99%
“…Studies have showed that E. coli O157:H7 survived for 13 weeks in lake water held at 15°C (93), while other studies have reported survival in farm water for up to 14 days at temperatures of <15°C (94), 70 days at 5°C, and 40 days at 21°C (95). In addition to temperature, the indigenous microflora (93), scarcity of nutrients (96), and protozoan predations also influence survival.…”
Section: Vtec In Watermentioning
confidence: 99%